2016
DOI: 10.1016/j.cegh.2015.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Effect of social and behavior change communication by using infotainment in community perception of adolescent girls for reproductive and sexual health care in high priority districts of Assam

Abstract: c l i n i c a l e p i d e m i o l o g y a n d g l o b a l h e a l t h 4 (2 0 1 6) 1 3 3-1 3 9

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 6 publications
1
24
0
1
Order By: Relevance
“…[13] Although effect of SBCC on increasing awareness among adolescents is known, there is gap in the documentation on effect of SBCC at the community level to increase awareness among adolescents. [1415] The formative research conducted as an approach for strengthening AH service delivery successfully generated evidence for guiding the development of a communication plan for AH. Similarly, the success of the model based on strengthening DCAH showed that ensuring an administrative will and adopting a governance and policy framework are essential for strengthening AH service delivery mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…[13] Although effect of SBCC on increasing awareness among adolescents is known, there is gap in the documentation on effect of SBCC at the community level to increase awareness among adolescents. [1415] The formative research conducted as an approach for strengthening AH service delivery successfully generated evidence for guiding the development of a communication plan for AH. Similarly, the success of the model based on strengthening DCAH showed that ensuring an administrative will and adopting a governance and policy framework are essential for strengthening AH service delivery mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…The study conducted by Mahanta et al . [11] demonstrated that social and behavior change communication was effective in increasing awareness on key nutrition and reproductive and sexual issues among adolescents; however, it captured few practice/behavior indicators and no outcome indicator. This study adds evidence on the intervention design and change in knowledge status of adolescents from Gujarat.…”
Section: Discussionmentioning
confidence: 99%
“…The number of studies undertaken in the region have also suggested beneficial effect of BCC. 51 The evidence synthesis of systematic reviews by Nair and colleagues 52 suggests that improving community participation and making local community aware about the healthcare rights have beneficial effect on maternal health outcomes. The review further states that BCC interventions delivered at home, use of mobile health technology, and nutrition targeted BCC along with food fortification are found to be effective.…”
Section: Usaidmentioning
confidence: 99%